A genome-based species taxonomy of the Lactobacillus genus complex - Wittouck, S. (2019)
Yes === There are more than 200 published species within the Lactobacillus genus complex (LGC), the majority of which have sequenced type strain genomes available. Although genome-based species delimitation cutoffs are accepted as the gold standard by the community, these are seldom actually checked for new or already published species. In addition, the availability of genome data is revealing inconsistencies in the species-level classification of many strains. We constructed a de novo species taxonomy for the LGC based on 2,459 publicly available genomes, using a 94% core nucleotide identity cutoff. We reconciled these de novo species with published species and subspecies names by (i) identifying genomes of type strains and (ii) comparing 16S rRNA genes of the genomes with 16S rRNA genes of type strains. We found that genomes within the LGC could be divided into 239 de novo species that were discontinuous and exclusive. Comparison of these de novo species to published species led to the identification of nine sets of published species that can be merged and one species that can be split. Further, we found at least eight de novo species that constitute new, unpublished species. Finally, we reclassified 74 genomes on the species level and identified for the first time the species of 98 genomes. Overall, the current state of LGC species taxonomy is largely consistent with genome-based species delimitation cutoffs. There are, however, exceptions that should be resolved to evolve toward a taxonomy where species share a consistent diversity in terms of sequence divergence. === This study was supported by the Research Foundation Flanders (grant 11A0618N), the Flanders Innovation and Entrepreneurship Agency (grants IWT-SB 141198 and IWT/50052), and the University of Antwerp (grant FFB150344).